Catheter-directed therapy for acute pulmonary embolism in children. (21st December 2018) - Akam-Venkata, Jyothsna; Forbes, Thomas J.; Schreiber, Theodore; Kaki, Amir; Elder, Mahir; Turner, Daniel R.; Kobayashi, Daisuke
Abstract: Background: Acute pulmonary embolism is a life-threatening condition and rarely occurs in children. In adults, catheter-directed therapy emerges as a potentially safer and effective therapeutic option. However, there is a paucity of data on the safety and efficacy of catheter-directed therapy for pulmonary embolism in children. We report a single-centred experience of catheter-directed therapy for acute pulmonary embolism in children. Methods: This is a retrospective study of children who had no CHD and underwent catheter-directed therapy at Detroit Medical Center during a 12-year period from 2005 to 2017. Demographic and clinical data associated with pulmonary embolism were collected along with the outcome. Results: A total of nine patients of median age 16 years with the range from 12 to 20 received catheter-directed therapy for sub-massive (n = 6) and massive pulmonary embolism (n = 3). Among nine patients, one patient received Angiojet thrombectomy and balloon angioplasty, whereas eight patients received catheter-directed thrombolysis using tissue plasminogen activator through infusion catheters (n = 3) or EkoSonic ultrasound-accelerated thrombolysis system (n = 5). In four out of five patients treated with EkoSonic, significant clinical improvement was noticed within 24 hours. Among seven patients who survived, two patients had minor gastrointestinal bleeding with median hospital stay of 8 days with the range from 5 to 24 days, and two patients with massive pulmonary embolism died possibly due to delayed institution of catheter-directed therapy. Conclusion: Catheter-directed therapy with/without EkoSonic is an emerging alternative therapy for sub-massive and massive pulmonary embolism in children. A timely institution of catheter-directed therapy appeared important to improve the outcome.